2016
DOI: 10.1016/j.ejmech.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel hybrids of highly potent and selective α4β2-Nicotinic acetylcholine receptor (nAChR) partial agonists

Abstract: We previously reported the cyclopropylpyridine and isoxazolylpyridine ether scaffolds to be versatile building blocks for creating potent α4β2 nicotinic acetylcholine receptor (nAChR) partial agonists with excellent selectivity over the α3β4 subtype. In our continued efforts to develop therapeutic nicotinic ligands, seven novel hybrid compounds were rationally designed, synthesized, and evaluated in [3H]epibatidine binding competition studies. Incorporation of a cyclopropane- or isoxazole-containing side chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In an related work, Zhang et al [12] described a series of novel ligands containing cyclopropane- or isoxazole- side chains onto the 5-position of 1-(pyridin-3-yl)-1,4-diazepine or 2-(pyridin-3-yl)-2,5-diazabicyclo [2.2.1]heptane which afforded compounds with selective partial agonist propertiers for α4β2* nAChR (K i of 0.5-51.4 nM), displaying also excellent selectivity over the α3β4 subtype. They also found that the most potent compounds, structurally exhibited a pyridine ring connected to a diazepine squeleton, where substituents at the 5-position of the pyridine core were found to be beneficial for the selectivity for α4β2 over α7 and ganglionic nAChRs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an related work, Zhang et al [12] described a series of novel ligands containing cyclopropane- or isoxazole- side chains onto the 5-position of 1-(pyridin-3-yl)-1,4-diazepine or 2-(pyridin-3-yl)-2,5-diazabicyclo [2.2.1]heptane which afforded compounds with selective partial agonist propertiers for α4β2* nAChR (K i of 0.5-51.4 nM), displaying also excellent selectivity over the α3β4 subtype. They also found that the most potent compounds, structurally exhibited a pyridine ring connected to a diazepine squeleton, where substituents at the 5-position of the pyridine core were found to be beneficial for the selectivity for α4β2 over α7 and ganglionic nAChRs.…”
Section: Resultsmentioning
confidence: 99%
“…Graph obtained for the displacement experiments of [ 3 H]-paroxetine for the synthesized compounds [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] in the cellular background h-SERT induced to 2.5 × 10 −5 M concentration. Fluoxetine (Flx) was used as a control for the compounds under study.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…15) displayed selectivity, as well as excellent antidepressant behavioral activity measured by the mouse forced-swim test. Zhang et al (2016) synthesized some hybrid compounds by combining substituted isoxazolyl side chains with N-pyridyldiamines as selective partial agonists for α4β2-nAChRs. Compound 84 (Fig.…”
Section: Antidepressant Activitymentioning
confidence: 99%
“…The chemistry of isoxazoles ( Fig. 1) has been an interesting field of study for decades because of their prominent potential as analgesic (Karthikeyan et al 2009), anti-inflammatory (Rajanarendar et al 2015;Banoglu et al 2016), anticancer (Kumbhare et al 2012;Tzanetou et al 2014), antimicrobial (Siddiqui et al 2013;Basha et al 2015), antiviral ), anticonvulsant (Frølund et al 2007), antidepressant (Yu et al 2012;Zhang et al 2016) and immunosuppressant . The literature survey revealed that the substitution of various groups on the isoxazole ring imparts different activity.…”
Section: Introductionmentioning
confidence: 99%